Do The Effects of Nudges Persist? Theory and Evidence from 38 Natural Field Experiments - Brandon, Alec; Ferraro, Paul J; List, John A; Metcalfe, Robert D; Price, Michael K; Rundhammer, Florian (Review of Economic Studies, 2026)
Abstract We formalize a research design to uncover the mechanisms underlying long-term reductions in energy consumption caused by a widely implemented nudge. We consider two channels: technology adoption and habit formation. Using data from 38 natural field experiments, we isolate the role of technology adoption by comparing treatment and control homes after the initial resident moves, which discontinues the treatment for a home. We find that fully half of energy reductions persist in the home after treatment ends and show this persistence is consonant with a technology adoption channel. The role of technology in creating persistent behaviour change has important implications for designing behavioural interventions and evaluating their long-term social impacts.